(untitled) (Research, Society and Development, 2024)
Dental antimicrobial stewardship is important in international efforts to combat antibiotic resistance and is therefore valuable in implementing AMS strategies in dental practices and outpatient clinics. The development of antibiotic prescribing guidelines with a clear description of the indications and ease of use of the regimen is necessary. The objective of this article is to present considerations regarding the knowledge on the prescription of antibiotics in endodontics by means of a narrative review carried out from searches in PubMed and MedLine databases using the following descriptors: endodontia, irreversible pulpite, antibiotics, periodontitis, abscess apical, infection.Articles published in 2015 and between 2020 and 2024 written in English and Portuguese were included. The articles selected after reading their abstract and checking their adequacy were added to the content of this review. Based on the considerations regarding this present review, it is possible to conclude that there is a need for continuing education programs on the use of antibiotics, international guidelines on antibiotic prophylaxis, prescription errors, antibiotic prescription and better prescription adequacy, debilitated patients at risk of developing bacterial endocarditis, chronic diseases that require prophylactic prescription before or during treatment, excessive prescription of antibiotics in cases of pulpitis and other unnecessary indications and prescription of antibiotics only performed in conditions of generalized edema formation, among others.